(untitled) (Comillas Journal of International Relations, 2014)
The development of a “country-brand Project” proceeds from two paths: by the development of its methodological and doctrinal basis, or by the principal concepts in which lies a public strategy, focus on the upgrading of the international reputation and its consequences on the perceptions and decisions of the most influencers actors in the political and economical world landscape. A “country reputation” means the “prelude of a right decision” in the context of a global and changing communication impulse, where data, social relations and media coverage, determine a “brain system of values” and its “strengths or preferences”. The Spanish Economy has passed a period of important adjustments, with positive recognition of world leaders. The project, in terms of institutional design, must be the guarantor of public-private cooperation oriented to a foreign recognition of the country awareness, the components of the brand-values and the public support of initiatives related with that purpose. This text includes a brief resume of design, start-implement and short life period, where most Spaniards has been concerned.